Evaluation of the regional choice initiative - Phillips, Andrea (Andrea R.) (Research report (Rand Corporation) ;, 2016)
School districts in Beaver County, Pennsylvania, have been working to improve student achievement by increasing students' exposure to more rigorous courses. In 2007, the Beaver Valley Intermediate Unit (BVIU), a regional educational-service agency, received funding for a five-year grant under the U.S. Department of Education's Voluntary Public School Choice program. The BVIU responded by developing, implementing, and evaluating the Regional Choice Initiative (RCI), a large-scale initiative designed and implemented in 17 school districts. The RCI sought to expand school choice--as well as provide opportunities for students in low-performing districts to learn in high-performing environments--for students in grades 7-12 by offering four programs: Open Seats, Dual Enrollment, Cyber Learning, and Academies for Success. The program ran for six years--2007-2008 to 2012-2013. The BVIU commissioned RAND to conduct a formative and a summative evaluation of these programs. The RAND team took a mixed-methods, quasi-experimental approach to evaluate the implementation and impact of the RCI initiative. Authors reviewed program documents, interviewed a number of stakeholders throughout the region, surveyed parents, and analyzed student RCI participation and administrative data. The RAND team also worked with the RCI team and partnering superintendents to develop the RCI logic model and set up performance measures for each RCI program to guide the implementation and evaluation of the RCI. RAND evaluated the performance of individual programs and RCI overall. The authors also identified aspects of implementation that facilitated or hindered the performance of the RCI.